2015
DOI: 10.3390/en81212407
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Performance Analysis of Novel Flux-Regulatable Permanent Magnet Machines for Wide Constant-Power Speed Range Operation

Abstract: Two novel structures of permanent magnet (PM) machine, namely a hybrid excitation flux modulation machine (HEFMM) and a variable flux memory machine (VFMM), which have excellent field-weakening capability, are presented in this paper. The HEFMM incorporates the advantages of parallel hybrid excitation structure and flux modulation structure, so as to increase the torque density as well as increase the constant-power speed range. Inspired by the HEFMM, aiming to further improve the efficiency of machine, the VF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Many researchers have proposed structural alterations such as single stator for surface and interior permanent magnets [6,7], double stator [11][12][13][14][15][16], and double rotor [17,18]. Gieras et al [6] observed that a surface permanent magnet with a single stator generator had a low inductance value, resulting in a narrow field weakening range and a low torque-generating current.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have proposed structural alterations such as single stator for surface and interior permanent magnets [6,7], double stator [11][12][13][14][15][16], and double rotor [17,18]. Gieras et al [6] observed that a surface permanent magnet with a single stator generator had a low inductance value, resulting in a narrow field weakening range and a low torque-generating current.…”
Section: Introductionmentioning
confidence: 99%
“…In order to efficiently produce electricity, high-efficiency machines are desired. Permanent magnet (PM) machines are extensively utilized as electrical generators in renewable applications, such as hydro and wind energies, due mainly to their outstanding advantages, for instance, high power density, high torque density, high reliability, and freedom from excitation loss [1,2]. These machines can be categorized into two types, namely, the stator permanent magnet machine and the rotor permanent magnet machine, depending on the location of the installed PM [3].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of windage losses is usually moderate, albeit not completely insignificant [5]. The electromagnetic analysis of an AFPMSM has been widely addressed [6][7][8][9][10]. For instance, several analytical models were developed to compute the iron losses accurately and in a fast way by Hemeida and Sergeant [11].…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, Coren et al [17] presented experimental data for the windage losses associated with a rotating disk in a rotor-stator cavity with a superimposed throughflow of air at high rotational Reynolds numbers up to the range of Re = 10 7 .…”
Section: Introductionmentioning
confidence: 99%